Giuseppe Toniolo - Guasco, Alberto (Rivista di storia della Chiesa in Italia, 2022)
This paper attempts to explore four crucial points of the relationship between Toniolo and Pisa during the First World War: 1) the main lines of Toniolo's historical-theological reflection on war times; 2) his participation in university life during the "useless massacre" years and his role when Pisa university gave assistance to other university towns, Venice and Padua, which had become frontline or rearguard towns; 3) Toniolo's contribution to the internal war front, in the context of the hospitality given to refugees fleeding to Pisa after the Caporetto defeat and his personal involvement in war mourning; 4) during the second Spanish flu wave in Italy, when the war victory was approaching, Toniolo's death as a convergence point of local and national expressions of mourning on the part of the Italian Catholic world.